Quantitative assessment of media concentration using the Homodyned K distribution - Cristea, Anca; Collier, Nicolas; Franceschini, Emilie; Mamou, Jonathan; Cachard, Christian; Basset, Olivier (Ultrasonics, 2020)
•Homodyned-K α parameter estimates obtained from both simulated and experimental ultrasound data were found to increase monotonically for concentrations of up to 40 scatterers per resolution cell.•Estimates of log(1/α) have a reduced variance by comparison and can be used to discriminate between the studied scatterer concentrations.•The above are valid when using at least 10.000 independent samples per estimation. The Homodyned K distribution has been used successfully as a tool in the ultrasound characterization of sparse media, where the scatterer clustering parameter α accurately discriminates between media with different numbers of scatterers per resolution cell. However, as the number of scatterers increases and the corresponding amplitude statistics become Rician, the reliability of the α estimates decreases rapidly. In the present study, we assess the usefulness of α for the characterization of both sparse and concentrated media, using simulated independent and identically distributed (i.i.d.) samples from Homodyned K distributions, ultrasound images of media with up to 68 scatterers per resolution cell and ultrasound signals acquired from particle phantoms with up to 101 scatterers per resolution cell. All parameter estimates are obtained using the XU estimator (Destrempes et al., 2013). Results suggest that the parameter α can be used to distinguish between media with up to 40 scatterers per resolution cell at 22 MHz, provided that parameter estimation can be performed on very large sample sizes (i.e., >10,000 i.i.d. samples).